Perception of educational actors: from face-to-face class to virtual classes in times of pandemic (Revista Innova Educación, 2024)
Introduction: experimentation is an essential tool in learning, allowing an explanation of how knowledge integrates within a scientific academic community. Objective: to analyze the perception of students, teachers, and administrative staff regarding the delivery of practical classes in General Chemistry through virtual modality (use of laboratories) at the State University of the Santa Elena Peninsula (UPSE) in Santa Elena, Ecuador, amidst the health emergency caused by COVID-19 during 2020. Methodology: a mixed approach with an exploratory scope was employed, utilizing survey techniques with an instrument consisting of 15 parametric questions (10 closed-ended and 5 open-ended), exhibiting a reliability of 0.767 in Cronbach's Alpha; the research was non-experimental, adopting a cross-sectional cohort, encompassing the entire sample (133 individuals). Results: Over 50% of educational stakeholders encountered difficulties adapting to the new educational system, highlighting the limited use of ICT. Conclusion: the COVID-19 pandemic exposed certain institutions' lack of readiness for remote learning, unveiling numerous challenges when transitioning from in-person to virtual classes across the educational community. While the quarantine was initially a temporary measure, it has been regarded as a starting point to envision the future of higher education, where virtuality could establish itself as a new norm.
Keywords: educational stakeholders; higher education; COVID-19 pandemic; transition; virtuality